2019
DOI: 10.1111/tri.13543
|View full text |Cite
|
Sign up to set email alerts
|

Association between post‐transplant donor‐specific antibodies and recipient outcomes in simultaneous liver–kidney transplant recipients: single‐center, cohort study

Abstract: There is a dearth of published data regarding the presence of post-transplant donor-specific antibodies (DSA), especially C1q-binding DSA (C1q+DSA), and patient and kidney allograft outcomes in simultaneous liver-kidney transplant (SLKT) recipients. We conducted a retrospective cohort study consisted of 85 consecutive SLKT patients between 2009 and 2018 in our center. Associations between presence of post-transplant DSA, including persistent and/or newly developed DSA and C1q+DSA, and all-cause mortality and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
(58 reference statements)
1
13
0
Order By: Relevance
“…(3) Our recent study (n = 85, 14% with posttransplant DSAs) showed that the presence of posttransplant DSAs was significantly associated with an increased risk of mortality (hazard ratio [HR], 5.15; 95% confidence interval [CI], 1.92-13.77) and composite outcomes that consisted of mortality, kidney allograft loss, and antibody-mediated rejection (HR, 5.95; 95% CI, 2.30-15.39). (4) Supporting our observation, the article by Piñeiro et al also indicated a higher kidney allograft rejection rate in the high sensitization group, (1) which might be a consequence of persistent posttransplant DSAs. This was supported by the findings of this article, a previous article by O'Leary et al, and our work ( Fig.…”
Section: To the Editorsupporting
confidence: 87%
See 3 more Smart Citations
“…(3) Our recent study (n = 85, 14% with posttransplant DSAs) showed that the presence of posttransplant DSAs was significantly associated with an increased risk of mortality (hazard ratio [HR], 5.15; 95% confidence interval [CI], 1.92-13.77) and composite outcomes that consisted of mortality, kidney allograft loss, and antibody-mediated rejection (HR, 5.95; 95% CI, 2.30-15.39). (4) Supporting our observation, the article by Piñeiro et al also indicated a higher kidney allograft rejection rate in the high sensitization group, (1) which might be a consequence of persistent posttransplant DSAs. This was supported by the findings of this article, a previous article by O'Leary et al, and our work ( Fig.…”
Section: To the Editorsupporting
confidence: 87%
“…In particular, class 2 DSAs were more likely found in recipients with longer hospital stay and were associated with worse kidney graft outcomes. (4,5) Because liver transplantation is a life-saving procedure, we support the current practice to perform SLKT regardless of the pretransplant immunological risk. However, posttransplant DSAs should be handled as a potentially modifiable risk factor of kidney allograft outcome after SLKT.…”
Section: To the Editormentioning
confidence: 65%
See 2 more Smart Citations
“…(1,2) However, the persistence of class 2 DSA after SLKT or the development of de novo DSA has been associated with worse outcomes. (3)(4)(5) It has been proposed that class 2 DSAs may not be absorbed by the liver, but this is not the only immunomodulatory mechanism driven by the liver. (6,7) In our study, 4 patients were determined to have posttransplant class 2 DSAs out of 10 patients who had class 2 DSAs before transplant.…”
Section: To the Editormentioning
confidence: 99%